2012
DOI: 10.1590/s0100-54052012000100005
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the risk of cocoa moniliasis occurrence in Brazil as the result of climate change

Abstract: RESUMOT he a im of this stu dy wa s to eva lu a te the potentia l risk of monilia sis occu rrence a nd the impa cts of clima te cha nge on this disease in the coming decades, should this pathogen be introduced in Brazil. To this end, climate favora bility ma ps were devised for the oc cu r renc e o f m oni lia sis, bo th for the pr esen t a nd fu t u re tim e. The future scenarios (A2 and B2) focused on the deca des of 2 020, 2 0 5 0 a nd 2 0 8 0 . T hese scena r ios we re obt a ined from six glo ba l clima t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…Thus, these regions do not reach the ideal temperature range for moniliasis development; however, they are not traditional areas for cacao cultivation. Moraes et al (2012) reported that, in Brazil, the development of moniliasis was more favorable from November to May between 1961 and 1990. This interval is compatible with the time of fruit development, which can lead to large production losses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these regions do not reach the ideal temperature range for moniliasis development; however, they are not traditional areas for cacao cultivation. Moraes et al (2012) reported that, in Brazil, the development of moniliasis was more favorable from November to May between 1961 and 1990. This interval is compatible with the time of fruit development, which can lead to large production losses.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the areas with the greatest climatic potential for the occurrence of Moniliophthora roreri are found in the Northeast region, especially in southern Bahia (Moraes et al, 2012). This study focused on the main cocoa-producing region in Southern Bahia, which presents high temperature and air relative humidity during most of the year, making it a high-risk region if the disease were introduced to Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Es necesario crear un cordón de control y monitoreo constante que permita alertas tempranas y detección de brotes incipientes. En caso contrario, M. roreri podría devastar los cultivos de cacao brasileños y bolivianos, como está comenzando a suceder en la actualidad [7,16,65].…”
Section: Conclusionesunclassified
“…However, some crop production systems will likely need to be adapted to higher temperature conditions, for example, cacao (Theobroma cacao) production systems, where new cultivars adapted to the new environmental conditions (e.g. better adapted to heat stress) may be required (Moraes et al 2012a). Moreover, climate change may also alter the effectiveness of genetic resistance of cacao cultivars, which currently show moderate disease resistance to moniliosis (caused by Moniliophthora roreri).…”
Section: Potential Adaptations Of Cropping Systemsmentioning
confidence: 99%
“…In addition, an adaptation option is to cultivate cacao intercropped with forest plant species, because cacao is well adapted to shade. However, shade may also modify the potential for moniliasis occurrence on cacao due to alternations of the microclimatic conditions including leaf temperature and wetness duration (Moraes et al 2012a). This example illustrates that future disease risk is not only dependent on the future climatic conditions, but also on the yet unknown alternations of the cropping system, which ultimately creates complex interactions of the crop with various biotic and abiotic factors.…”
Section: Potential Adaptations Of Cropping Systemsmentioning
confidence: 99%